2020
DOI: 10.1002/marc.202000454
|View full text |Cite
|
Sign up to set email alerts
|

Isomeric Effect of Wide Bandgap Polymer Donors with High Crystallinity to Achieve Efficient Polymer Solar Cells

Abstract: Owing to the great advantages of lightweight, low cost, flexibility, semitransparency, and the large-area device fabrication, polymer solar cells (PSCs) have attracted considerable attention during the past decades. [1-7] Benefiting from the vigorous

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…In addition, comparing the two NFREAs, it was found that the stronger electron-donating ability of the DTSi unit in the 2T2CSi-4F molecular framework led to shallower lowest unoccupied molecular orbital (LUMO) levels, and the stronger O···S interaction led to better coplanarity. The good molecular planarity is also advantageous to enhancing intermolecular interaction, improving molecular crystallinity and charge transport. As expected, the facile synthesized NFREAs 2T2CSi-4F and 4T2CSi-4F exhibit good planarity, strong absorption in the region of 600–850 nm, and suitable energy levels, which can be well matched with the donor PBDB-T. In addition, compared to the asymmetrical 4T2CSi-4F, 2T2CSi-4F with a symmetrical structure has more red-shifted absorption, a smaller optical band gap of 1.45 eV, shallower LUMO energy levels, and better crystallinity.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…In addition, comparing the two NFREAs, it was found that the stronger electron-donating ability of the DTSi unit in the 2T2CSi-4F molecular framework led to shallower lowest unoccupied molecular orbital (LUMO) levels, and the stronger O···S interaction led to better coplanarity. The good molecular planarity is also advantageous to enhancing intermolecular interaction, improving molecular crystallinity and charge transport. As expected, the facile synthesized NFREAs 2T2CSi-4F and 4T2CSi-4F exhibit good planarity, strong absorption in the region of 600–850 nm, and suitable energy levels, which can be well matched with the donor PBDB-T. In addition, compared to the asymmetrical 4T2CSi-4F, 2T2CSi-4F with a symmetrical structure has more red-shifted absorption, a smaller optical band gap of 1.45 eV, shallower LUMO energy levels, and better crystallinity.…”
Section: Introductionmentioning
confidence: 56%
“…The synthesis routes of the NFREAs 2T2CSi-4F and 4T2CSi-4F are presented in Scheme . The key compound 3 was prepared according to the previously reported procedures. Then, 2T2CSi-4F and 4T2CSi-4F can be easily synthesized with overall yields of 44 and 25%, respectively, through a three-step or four-step synthesis route starting from 2T2C-2Br, and the detailed experiment is depicted in the Supporting Information. As depicted, the nonfused cores (i.e., compound 5 and compound 6) were prepared by Stille cross-coupling of compound 3 with DTSi and TT derivative tin reagents.…”
Section: Resultsmentioning
confidence: 99%
“…To get deep insight into the reason for IT-4F, Y6, and DTPC-DFIC possessing different planar structures, we carried out topological analysis of the electron density with the analysis of the bond critical point (BCP) based on the atoms-in-molecules (AIM) theory, as shown in Figure . A BCP (3, −1), which is a requirement for the presence of bonding interactions, is found between H···π, S···O, S···H, and H···H in IT-4F, Y6, and DTPC-DFIC, which demonstrates the existence of four kinds of intramolecular interactions.…”
Section: Results and Discussionmentioning
confidence: 99%
“…[43][44][45] Within the numerous D-p-A copolymers, the extensively used conjugated p bridge ranged from the simple ethylene 46 and ethynylene 47 to the aromatic thiophene, 45,[48][49][50][51][52][53] selenophene, 54,55 furan, 56 thiazole, 44,57,58 and larger conjugation thieno[3,2-b]thiophene (TT). 59,60 Of these, thiophene was regarded as the most common and successful application unit, due to its medium electronegativity, tunable distortion angle with the bilateral-linked groups, weak intermolecular SÁ Á ÁX (X = N, O, S, and halide) non-bonding interaction 61 and easily decorated by alkyl-, 62 alkyloxy-, 63 alkylthio-, 61,64 fluoro-, 45 chloro-, 51 ester 65 and siloxane-terminated 40 (OD) in NT812, the anticipated face-on orientation, and ideal microstructural morphology was formed, which impelled the relevant PCE, remarkably increasing from 3.03% to 10.33%. 62 In thieno [3,4-b]thiophene-based CPs, the broadened absorption, good planarity, and 11.9 times enhanced hole mobility, and thus 2.17 times increased PCE was observed after the alkyl was substituted with alkylthio chain.…”
Section: Introductionmentioning
confidence: 99%